Answer:
see explanation
Step-by-step explanation:
∠ a and ∠ b are a linear pair and sum to 180° , that is
∠ a + ∠ b = 180° ( substitute ∠ a = 42° )
42° +∠ b = 180° ( subtract 42° from both sides )
∠ b = 138°
∠ c and ∠ a are vertically opposite angles and are congruent (equal ), so
∠ c = ∠ a = 42°
∠ d and ∠ b are vertically opposite angles and are congruent , so
∠ d = ∠ b = 138°
∠ e and ∠ a are corresponding angles and are congruent , so
∠ e = ∠ a = 42°
∠ f and ∠ b are corresponding angles and are congruent , so
∠ f = ∠ b = 138°
∠ g and ∠ e are vertically opposite angles and are congruent , so
∠ g = ∠ e = 42°
∠ h and ∠ f are vertically opposite angles and are congruent , so
∠ h = ∠ f = 138°
Then
∠ b = 138° , ∠ c = 42° , ∠ d = 138° , ∠ e = 42° , ∠ f = 138° , ∠ g = 42° , ∠ h = 138°